Corrections to Phytotaxa 197: A revised delimitation of the rattan genus Calamus (Arecaceae) - Baker, William (Phytotaxa, 2015)
In Phytotaxa 197 (Baker 2015), I placed the rattan genera Ceratolobus Blume (in Schultes & Schultes 1830: lxxx), Daemonorops Blume (in Schultes & Schultes 1830: 1333) and Pogonotium Dransfield (1980: 763) in synonymy with Calamus Linnaeus (1753: 325). Subsequently, two nomenclatural errors and one overlooked synonym have been drawn to my attention. These are corrected here.